Synthesis of an acridine orange sulfonamide derivative with potent carbonic anhydrase IX inhibitory action - Marco Bragagni; Fabrizio Carta; Sameh M. Osman; Zeid AlOthman; Claudiu T. Supuran (Taylor & Francis Group, 2017)
Acridine orange (AO) a fluorescent cationic dye used for the management of human musculoskeletal sarcomas, due to its strong tumoricidal action and accumulation in the acidic environment typical of hypoxic tumors, was used for the preparation of a primary sulfonamide derivative. The rationale behind the drug design is the fact that hypoxic, acidic tumors overexpress carbonic anhydrase (CA, EC 4.2.1.1) isoforms, such as CA IX, which is involved in pH regulation, proliferation, cell migration and invasion, and this enzyme is strongly inhibited by primary sulfonamides. The AO-sulfonamide derivative was indeed a potent, low nanomolar CA IX inhibitor whereas its inhibition of the cytosolic isoforms CA I and II was in the micromolar range. A second transmembrane, tumor-associated isoform, CA XII, was also effectively inhibited by the AO-sulfonamide derivative, making this compound an interesting theranostic agent for the management of hypoxic tumors.